2021
DOI: 10.1057/s41287-021-00362-8
|View full text |Cite
|
Sign up to set email alerts
|

Women’s Changing Opportunities and Aspirations Amid Male Outmigration: Insights from Makueni County, Kenya

Abstract: In Makueni County, Kenya, an area experiencing intensifying migration flows, we investigate the aspired futures of rural men and women using a novel methodology combining a narrative-based survey tool, focus group discussions and semi-structured interviews. Our findings indicate that, in the absence of men and presence of norms restricting women's movement out of rural life, women are becoming increasingly engaged in farm management. Women’s aspirational narratives focused on commercialising farm activities, l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 33 publications
(41 reference statements)
0
16
0
Order By: Relevance
“…Furthermore, we found that women are heavily involved in uptake decisions, including those regarding tree planting, and that even women with resident husbands may be able to contest restoration decisions. These findings challenge the narrative that men in eastern Kenya are the chief decision-makers over farming and tree planting (Muok et al 1998, Kiptot et al 2014, and likely reflect women's increased participation in agricultural workshops and farm management in the absence of their male relatives (Crossland et al 2021). Similar to other studies, our findings indicate that when women attend agricultural workshops and are allowed to implement their knowledge, they gain more confidence and recognition that can lead to greater agency in farming decisions (Nyasimi andHuyer 2017, Bullock andTegbaru 2019).…”
Section: Changes In the Wider Social Context Of On-farm Restorationmentioning
confidence: 62%
See 1 more Smart Citation
“…Furthermore, we found that women are heavily involved in uptake decisions, including those regarding tree planting, and that even women with resident husbands may be able to contest restoration decisions. These findings challenge the narrative that men in eastern Kenya are the chief decision-makers over farming and tree planting (Muok et al 1998, Kiptot et al 2014, and likely reflect women's increased participation in agricultural workshops and farm management in the absence of their male relatives (Crossland et al 2021). Similar to other studies, our findings indicate that when women attend agricultural workshops and are allowed to implement their knowledge, they gain more confidence and recognition that can lead to greater agency in farming decisions (Nyasimi andHuyer 2017, Bullock andTegbaru 2019).…”
Section: Changes In the Wider Social Context Of On-farm Restorationmentioning
confidence: 62%
“…Similarly, 49% of Makueni participants reported having a secondary source of income from off-farm activities, compared to only 35% and 22% in Kitui and Machakos counties, respectively. This likely reflects the high rates of male outmigration and off-farm employment found in Makueni County (Crossland et al 2021). Households in Kitui were also less well-off than in Machakos and Makueni counties, in that they were more dependent on food aid, less connected and live in less permanent housing.…”
Section: Farmer and Household Characteristicsmentioning
confidence: 99%
“…Yet, aspirations are not purely shaped by individual desires (Huijsmans et al 2020). Social pressures, norms and expectations also play a role in their formation and expression (Bennike et al 2020;Crossland et al 2021). For example, in many communities 'farming' is not only an income generation activity but is also perceived as a lifestyle.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Makueni is the only county in which most people see themselves farming more than half of their time. This may be, at least partially, explained by the high number of female respondents in this site (64% women) and the feminised nature of farm management in the county amid increasing male-outmigration (see Crossland et al 2021).…”
Section: Livelihood Strategiesmentioning
confidence: 99%
See 1 more Smart Citation